Lung abscess preceded by fever of unknown origin: a case report - Buntara, Ivan; Hidayat, Sari Purnama; Buulolo, Christina Siuwandy; Hendsun (International Journal of Advances in Medicine, 2023)
Lung abscess is a condition that characterized by formation of pus or tissue necrosis in lung parenchyma. The prevalence of lung abscess in Indonesia is still unknown, but the incidence seems to be decreased. Lung abscess could be categorized in many forms based on the duration, etiology and the way of spreading. Early sign and symptoms usually cannot be differentiated from pneumonia. Lung abscess also could be preceded by fever of unknown origin, so it could be challenging to diagnose. This case report presented a-57-years old man that preceded by fever of unknown origin. Chest X-ray show unspecified lung infiltrate, thus treated as a pneumonia. Further X-ray showed the clear image of cavities with abscess. Lung CT-scan was performed and bronchiectasis also lung abscess were found. Comprehensive history taking, physical examinations and diagnostic tests were done in this patient until the diagnosis is established.